Count - Martínez, Valerie, 1961- (Camino del sol., 2021)
"Count is a book-length narrative poem driven by love and wonder for the natural world, the urgency of climate change, and the wisdom and warning of flood stories passed down to us by ancestors. Ecology and science are deftly interwoven with mythology and personal history to create a panorama of an apocalyptic future we inevitably will have to confront. The central figure and speaker seeks to understand how humans reckon with the environment and our role in its devastation through various forms of counting, such as the relationships between an integer and infinity, between an individual and their community, or how one degree in temperature can determine whether sediments become sand or stone, and how the difference between high desert and low alpine is only a matter of inches. Downward counts signal the frightening countdown to climate disaster and looming extinction, and upward counts are used to measure the stunning beauty and complexity of flora and fauna. The book is divided into 35 numbered sections that combine to create an an ecopoetic acutely connected to the damage caused by humans to our planet, and the resulting trauma inflicted upon the natural world, both past and present"--